STRATEGI PENINGKATAN INDEKS PEMBANGUNAN MANUSIA (IPM) DI KOTA CILEGON - Alwin Setiawan (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2025)
The gap in human development achievements between regions in Banten Province indicates the need for special strategies for areas like Cilegon City to accelerate the improvement of the Human Development Index (HDI). This research aims to analyze the Human Development Index (HDI) achievement of Cilegon City, evaluate its constituent components, identify influencing factors, and formulate strategies for HDI improvement based on SWOT analysis. The HDI achievement of Cilegon City in 2024 is 78.83, categorized as